Atomoxetine Open-Label Trial in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Atomoxetine (originally named tomoxetine), a new therapy for attention deficit hyperactivity disorder (ADHD) marketed by Eli Lilly, was compared to methylphenidate in a prospective, randomized, open-label study for 10 weeks duration, at the University of Nebraska Medical Center, Massachusetts General Hospital, Mount Sinai Medical Center, Carolinas Medical Center, and Lilly Research Laboratories.